2020
DOI: 10.1186/s12904-020-00547-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the duration of the palliative care period on cancer patients with regard to the use of hospital services and the place of death: a retrospective cohort study

Abstract: Background: In order to avoid unnecessary use of hospital services at the end-of-life, palliative care should be initiated early enough in order to have sufficient time to initiate and carry out good quality advance care planning (ACP). This single center study assesses the impact of the PC decision and its timing on the use of hospital services at EOL and the place of death. Methods: A randomly chosen cohort of 992 cancer patients treated in a tertiary hospital between Jan 2013-Dec 2014, who were deceased by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…A Finnish study looked at the duration between the decision for treatment with a palliative intent and the patient subsequently dying, which they found to be, on average, 46 days; most patients had a GOC with an appropriate code status assigned, but these decisions were found to have been taken closer to the point of the patient dying than they had aimed for. 18 Although not statistically significant, there was an increase in the number of patients identified as having a palliative intent for treatment post-MED-REM intervention; following through with the appropriate referrals for patients with this intent established is important to ensure that good palliation is achieved prior to the terminal phase of the disease and not just as a consequence of a deterioration in condition.…”
Section: Discussionmentioning
confidence: 94%
“…A Finnish study looked at the duration between the decision for treatment with a palliative intent and the patient subsequently dying, which they found to be, on average, 46 days; most patients had a GOC with an appropriate code status assigned, but these decisions were found to have been taken closer to the point of the patient dying than they had aimed for. 18 Although not statistically significant, there was an increase in the number of patients identified as having a palliative intent for treatment post-MED-REM intervention; following through with the appropriate referrals for patients with this intent established is important to ensure that good palliation is achieved prior to the terminal phase of the disease and not just as a consequence of a deterioration in condition.…”
Section: Discussionmentioning
confidence: 94%
“…The number of patients fulfilling the criteria was 221. This study is continuum to a recently published Finnish study (17). However, in the previous study, the larger cancer entities dominated and only a part of the pancreatic cancer patients were included.…”
Section: Methodsmentioning
confidence: 97%
“…In a recent Finnish study, late or lacking PC decision-making was found to be associated with more aggressive care close to death (16). PC intervention and an early PC decision have been shown to be associated with a drop in hospitalizations and visits to the emergency department (ED) during the last month of life, also creating cost benefits (17,18). Starting a new anticancer treatment or continuing ongoing treatment very close to death, repeated ED visits, inpatient hospital admissions, or intensive care unit stays near the EOL have been considered indicators of a poor quality of life (19).…”
Section: ) Conclusion: a Late Or Lacking Pc Decision For Patients Wit...mentioning
confidence: 99%
“…3 The benefits of early PC are numerous and well studied in high-income settings, including improved quality of life and increased value in healthcare spending. [4][5][6] However, these outcomes are missing from low-and-middleincome countries (LMIC) and with it, the momentum to increase publicly available PC. [7][8][9] We therefore designed a pilot, feasibility randomised controlled trial (RCT) of early PC in newly diagnosed cancer patients in Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care (PC) aims to reduce pain and suffering for those with incurable disease 3. The benefits of early PC are numerous and well studied in high-income settings, including improved quality of life and increased value in healthcare spending 4–6. However, these outcomes are missing from low-and-middle-income countries (LMIC) and with it, the momentum to increase publicly available PC 7–9.…”
Section: Introductionmentioning
confidence: 99%